Unforeseen Outcomes Post Treatment for Radiation Induced Trismus: A Case Report - Akash Sivam; Ankit Garg; Paul Sillifant (Medicines, 2022)
Post radiotherapy radiation trismus presents significant concerns for a patient’s quality of life and for the clinical monitoring for recurrence of head and neck oncology. Current treatments include scar band release surgery that has been shown to be safe and effective. We present a case with a rare, post-operative complication of difficulty of mouth closure that can pose a significant impact on quality of life that should be considered.